2007
DOI: 10.1111/j.1420-9101.2006.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Sounds different: inbreeding depression in sexually selected traits in the cricket Teleogryllus commodus

Abstract: If male sexual signalling is honest because it captures genetic variation in condition then traits that are important mate choice cues should be disproportionately affected by inbreeding relative to other traits. To test this, we investigated the effect of brother–sister mating on advertisement calling by male field crickets Teleogryllus commodus. We quantified the effect of one generation of inbreeding on nightly calling effort and five finer‐scale aspects of call structure that have been shown to influence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 50 publications
4
47
1
Order By: Relevance
“…In the few species studied, inbreeding has caused reductions to some, but not necessary all, potential sexual signals. Generally, those signals that are under the strongest sexual selection seem to be mostly affected by inbreeding (Sheridan and Pomiankowski 1997;Aspi 2000;van Oosterhout et al 2003 but see Drayton et al 2007). In fact, one of the suggested ways for resolving the condition dependence of the sexual signaling relies on the sensitivity of the sexual signals to inbreeding (Cotton et al 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the few species studied, inbreeding has caused reductions to some, but not necessary all, potential sexual signals. Generally, those signals that are under the strongest sexual selection seem to be mostly affected by inbreeding (Sheridan and Pomiankowski 1997;Aspi 2000;van Oosterhout et al 2003 but see Drayton et al 2007). In fact, one of the suggested ways for resolving the condition dependence of the sexual signaling relies on the sensitivity of the sexual signals to inbreeding (Cotton et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…in Teleogryllus commodus, Hunt et al 2004b), did not indicate inbreeding depression and was not affected by any other explanatory variables. Potential reasons for the lack of inbreeding depression might be the earlier elimination (by death) of inbred individuals with reduced total time spent calling, ad libitum food conditions, or low statistical power (all of these are discussed by Drayton et al 2007). An alternative reason could be the altered life history decisions of males.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is becoming clear that traits important in sexual selection might have significantly higher inbreeding depression than morphological and life-history traits (Oosterhout & Trigg 2003). In T. commodus, fine-scale parameters of male calling song were influenced by inbreeding depression by as much as 350% (Drayton et al 2007). Depending on how these signalling parameters contribute to net fitness, the costs of inbreeding could be considerably higher than the data on morphological and lifehistory variables would suggest, negating any inclusive fitness benefits of mating with siblings, and favouring inbreeding avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…It has, indeed, been shown that sexual signals were inbreeding-dependent in studies on fish and invertebrates [18][19][20][21]. However, studies on birds that experimentally test if the expression of song is inbreeding-dependent are extremely rare (but see [22]), despite the pre-eminent role of bird song as a model to study sexually selected traits.…”
Section: Introductionmentioning
confidence: 99%